Effect of Using Date By-product with Enzyme on Performance and Blood Parameter of Broiler - Jassim , Jaffer M. (International Journal of Poultry Science, 2010)
Effect of date by-product on productive and blood characteristic was studied in broiler chicks. Seven formulated diets contained (0, 5, 10 and 15) % date by-product without enzyme and (0, 5, 10 and 15) % date by-product with enzyme instead of yellow corn. A total of 210 one-day old chicks were used for 42 days. Body weight, feed intake, feed conversion and economic figure were not significantly effects by using date by-product. However, total protein, albumin, globulin and glucose in serum blood showed significant (p